2021
DOI: 10.1186/s12909-021-02777-7
|View full text |Cite
|
Sign up to set email alerts
|

Interns’ perspectives on impacts of the COVID-19 pandemic on the medical school to residency transition

Abstract: Background The COVID-19 pandemic resulted in disruptions to medical school training and the transition to residency for new post-graduate year 1 resident-physicians (PGY1s). Therefore, the aim of this study was to understand the perspectives of United States PGY1s regarding the impact of the pandemic on these experiences. Our secondary aims were to understand how desire to practice medicine was impacted by the pandemic and whether PGY1s felt that they were able to meaningfully contribute to the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
20
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 23 publications
1
20
0
1
Order By: Relevance
“…Third, senior residents (PGY ≥4) reported less depression than junior residents (p = 0.049). This finding corroborates with previous publications which showed that senior residents experienced a lesser degree of anxiety (Rana et al, 2020), and that the majority of interns (PGY1) reported disrupted social connectedness and educational experiences during the pandemic, particularly those with health concerns and children (Winn et al, 2021).…”
Section: Discussionsupporting
confidence: 92%
“…Third, senior residents (PGY ≥4) reported less depression than junior residents (p = 0.049). This finding corroborates with previous publications which showed that senior residents experienced a lesser degree of anxiety (Rana et al, 2020), and that the majority of interns (PGY1) reported disrupted social connectedness and educational experiences during the pandemic, particularly those with health concerns and children (Winn et al, 2021).…”
Section: Discussionsupporting
confidence: 92%
“…A study assessing the COVID-19’s impact on post-graduate year 1 (PGY-1) physicians showed a generally unfavorable effect on medical training, as high as 77% taking a dim view in connection with the medical school community and 55% regarding preparation for the intern year [ 15 ]. We found that 75% of the study participants believed that COVID-19 had a negative impact on their overall educational experience.…”
Section: Discussionmentioning
confidence: 99%
“…It is also evident that the support of fellows of a similar age and the effective use of simulation-based education can improve the readiness of the residents [ 16 , 17 ]. With regard to the transition to residency during the COVID-19 pandemic, residents who graduated early, because of a sense of responsibility or financial motivation and went on to work on the front lines, perceived their experience as positive and felt that they should be given future opportunities to monitor and improve their skills [ 18 , 19 ]. Although there is little research on how the mismatch between residents and supervisors in the transition to residency can be addressed [ 20 ], we can bridge this gap by exploring the thoughts and perspectives of such residents—who experienced interruptions in undergraduate clinical training due to the pandemic and had just started their postgraduate training—to establish the necessary support.…”
Section: Introductionmentioning
confidence: 99%